Ministry of Finance Decree No. 347 of the year 2010 Amending Certain Provisions Of The Executive Regulations Of The Law On Organizing Bids And Tenders Promulgated By Decree No. 1367 Of The Year 1998 = وزارة المالية قرار رقم 347 لسنة 2010 بتعديل بعض أحكام اللائحة التنفيذية لقانون تنظيم المناقصات والمزايدات الصادرة بالقرار رقم 1367 لسنة 1998 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.